2019
DOI: 10.15390/eb.2019.7820
|View full text |Cite
|
Sign up to set email alerts
|

Middle and High School Students' Opinions, Experiences and Responses Regarding to Cyberbullying

Abstract: Bu araştırmanın amacı, öğrencilerin siber zorbalığa yönelik görüşlerini, siber zorbalık deneyimlerini ve siber zorbalığa dâhil olma rollerine göre, olaylara müdahale etme davranışlarını belirlemektir. Araştırmanın çalışma grubu 11-17 yaş arasındaki 952 öğrenciden oluşmaktadır. Veri toplama aracı olarak "Siber zorbalık farkındalık anketi-öğrenci formu" kullanılmıştır. Veriler 2016-2017 eğitim-öğretim yılının ikinci döneminde toplanmıştır. Araştırma sonunda öğrencilerin, siber zorbalık davranışları, siber zorbal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
3
0
2
Order By: Relevance
“…Some studies have stated that teenagers tend to share the cyberbullying experience with their friends rather than with their parents (Dehue et al, 2008;Juvonen & Gross, 2008;Patchin & Hinduja, 2006). In another study conducted by Kalender et al (2019), it was stated that students exposed to cyberbullying mention it to their parents, friends, and to their teachers. Kristensen and Smith (2003) pointed out that teenagers prefer seeking social help against and withdrawing from cyberbullying behaviors; but that as their age advances, they tend to develop more effective solutions in tackling cyberbullying.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have stated that teenagers tend to share the cyberbullying experience with their friends rather than with their parents (Dehue et al, 2008;Juvonen & Gross, 2008;Patchin & Hinduja, 2006). In another study conducted by Kalender et al (2019), it was stated that students exposed to cyberbullying mention it to their parents, friends, and to their teachers. Kristensen and Smith (2003) pointed out that teenagers prefer seeking social help against and withdrawing from cyberbullying behaviors; but that as their age advances, they tend to develop more effective solutions in tackling cyberbullying.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this is that, even if student victims remain physically distant from cyberbullies at school, they are unable to prevent violence aimed at them within virtual platforms, and cyber-aggressors can therefore continue to send disturbing or threatening messages through mobile phones or computers to their target victim. In addition, it has been identified that if students witness cyberbullying in their class, they exhibit behaviors such as "trying to stop such actions" or "helping the victim of such actions" (Kalender, Keser, & Tugun, 2019;Kildow, 2008). In addition, individuals who are exposed to cyberbullying can be ostracized by their friends, and may even break off friendships due to feelings of sadness, stress or the anxiety they may be experiencing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…La incidencia del género y edad en el ciberacoso ha sido discutida en la literatura científica. Distintos trabajos señalan a los chicos como principales agresores (Cardozo, Dubini, & Lorenzino, 2017;Kavuk Kalender, Keser, & Tugun, 2019;Pérez Vallejo, 2017) y a las chicas como principales víctimas (Cardozo, Dubini, & Lorenzino, 2017;González-Calatayud, 2018), aunque otras evidencias sostienen la inexistencia de diferencias de género en esta conducta (González Calatayud & Prendes Espinosa, 2018;Wadian, Jones, Sonnentag, & Barnett, 2016). En cuanto a la edad, los resultados confirman que el ciberacoso se da con mayor frecuencia entre los 13 y los 15 años (De-Barros Ventura, Rodríguez-García, & Sola Reche, 2018; Garaigordobil M. , 2015) y que son las mujeres las más acosadas en esta franja etaria (Rodríguez Domínguez, Martínez-Pecino, & Durán, 2015).…”
Section: Ciberacosounclassified
“…Kapsamlı tanımlamalardan biri Mason (2008, s.323) tarafından, "Siber zorbalık, bir birey veya bir grubun, başka bir birey veya grubu kasıtlı ve tekrar eden bir şekilde taciz veya tehdit etmek amacıyla iletişim teknolojilerini rahatsız edici metin, görüntü gönderme veya yayınlama yoluyla bilinçli olarak kullanması" biçiminde gerçekleştirilmiştir. Siber zorbalık, herhangi birine zarar vermek için bir amaç doğrultusunda ve tekrarlayan biçimde bilgi ve iletişim teknolojilerini kullanarak bireylerin saldırganlık davranışları sergilemeleri olarak ifade edilmektedir (Beran ve Li, 2005;Kavuk-Kalender, Keser ve Tugun, 2019). Siber zorbalık farklı biçimlerde açığa çıkabilmektedir.…”
Section: Introductionunclassified